Europatrida - Francisco de Oliveira (Outros Títulos, 2019)
This volume brings together contributions from authors from sixteen European countries who seek their roots in the classical Greek heritage and especially in literary or epigraphic texts written in ancient Greek, Byzantine, Renaissance or later eras. With this they seek to clarify the idea of their own nationality in the context of the construction of a multifaceted Europe with a historical personality, from the past to the present.